Presynaptic calcium signalling in cerebellar mossy fibres - Thomsen, Louiza B.; Jörntell, Henrik; Midtgaard, Jens (Frontiers in Neural Circuits, 2010)
Whole-cell recordings were obtained from mossy fibre terminals in adult turtles in order to characterize the basic membrane properties. Calcium imaging of presynaptic calcium signals was carried out in order to analyse calcium dynamics and presynaptic GABA B inhibition. A TTX-sensitive fast Na+ spike faithfully followed repetitive depolarizing pulses with little change in spike duration or amplitude, while a strong outward rectification dominated responses to long-lasting depolarizations. High-threshold calcium spikes were uncovered following addition of potassium channel blockers. Calcium imaging using Calcium-Green dextran revealed a stimulus-evoked all-or-none tetrodotoxin (TTX) -sensitive calcium signal in simple and complex rosettes. All compartments of a complex rosette were activated during electrical activation of the mossy fibre, while individual simple and complex rosettes along an axon appeared to be isolated from one another in terms of calcium signalling. CGP55845 application showed that GABA B receptors mediated presynaptic inhibition of the calcium signal over the entire firing frequency range of mossy fibres. A paired-pulse depression of the calcium signal lasting more than one second affected burst firing in mossy fibres; this paired-pulse depression was reduced by GABA B antagonists. While our results indicated that a presynaptic rosette electrophysiologically functioned as a unit, topical GABA application showed that calcium signals in the branches of complex rosettes could be modulated locally, suggesting that cerebellar glomeruli may be dynamically sub-compartmentalized due to ongoing inhibition mediated by Golgi cells. This could provide a fine-grained control of mossy fibre-granule cell information transfer and synaptic plasticity within a mossy fibre rosette.